62 A comparison of percutaneous and surgical revascularisation strategies following an equipoise decision in a heart team meeting. (4th June 2021) - Mailey, Jonathan; Ahmed, Mahmoud; Shahmohammadi, Michael; Murphy, Conleth
Abstract : Introduction: Current guidelines advocate a Heart Team (HT) approach to decision making in complex coronary artery disease (CAD). Available evidence suggests that PCI is non-inferior to surgery in patients with three vessel or left main stem disease in the setting of a low-intermediate anatomical syntax score. The majority of HT discussions result in a recommendation of percutaneous coronary intervention (PCI) or coronary artery bypass surgery (CABG), however a decision is deemed to be equipoised when one revascularisation strategy is not felt to carry significant prognostic benefit. In this study we sought to evaluate clinical outcomes following an equipoise decision in a Heart Team meeting. Methods: This was a single centre retrospective study. All patients requiring intervention for structural heart disease in addition to CAD were excluded. Between January 2015 and December 2018 a total of 134 patients were deemed to be equipoise following discussion at a Heart Team meeting (7.1% of all discussions). Demographics, procedural details and clinical outcomes were obtained from our national electronic health care record. The primary outcome was the 3-year rate of major adverse cardiovascular and cerebrovascular events (MACCE). This was a composite of cardiovascular death, non-procedural myocardial infarction (MI), stroke and unplanned revascularisation. Results: A total of 108 patients underwent PCI and 26 CABG. Mean follow-up was 1177±384 days in the PCI cohort and 1201±349 days in the CABG cohort (p=0.77). Baseline demographics did not differ significantly with the exception of chronic kidney disease and CAD involving 3 vessels ( tables 1 & 2 ). In the PCI cohort advanced calcium modification (intravascular lithotripsy or rotablation) was performed in 11.1% of procedures and intravascular imaging in 58.3%. The mean number of stents used was 3.3±1.5 and total stent length was 97.0±47.5mm. The 3-year MACCE rate was 14.3% in the PCI cohort and 11.5% in the CABG cohort (p=0.76) ( figure 1 ). 3-year cardiovascular death (PCI 2.8% vs CABG 0.0%, p=0.39) and unplanned revascularisation (PCI 11.5% vs CABG 7.9%, p=0.62) rates were numerically higher with PCI, whereas non-procedural MI (PCI 6.6% vs CABG 7.7%, p=0.85) and stroke (PCI 0.9% vs CABG 3.8%, P=0.27) rates were numerically higher with CABG. None of these differences met statistical significance. The incidence of stent thrombosis at 1-year was 1.9% in the PCI cohort. PCI resulted in a reduction in total length of stay (10.9±4.9 days in the inpatient PCI vs 34.3±15.5 days in the inpatient CABG cohorts, p<0.001). Conclusions: This study demonstrated no difference in MACCE between revascularisation modalities in patients with complex CAD deemed to be clinically equipoised following HT discussion. These results suggest that PCI is non-inferior to CABG in this population and provide validation to the decision making process of the HT in real life. Conflict of Interest: nil